Exposure of stevia (Stevia rebaudiana B.) to silver nanoparticles in vitro: transport and accumulation - Celia G. Castro-González (Nature Portfolio, 2019)
Abstract The impact of nanotechnology in the field of agricultural sciences creates the need to study in greater detail the effect of products offering nanoparticles for application in plant species of agricultural interest. The objective of this study was to determine the response of stevia (Stevia rebaudiana B.) in vitro to different concentrations of AgNPs (silver nanoparticles), as well as to characterize and identify their absorption, translocation and accumulation mechanisms. Nodal segments of stevia grown in MS medium supplemented with AgNPs (0,12.5, 25, 50,100 and 200 mg L−1) were used. After 30 days of in vitro shoot proliferation, the number of shoots per explant, shoot length, chlorophyll content, dry matter content and the metallic silver (Ag) content of the plants were quantified. In addition, characterization, transport and accumulation of silver nanoparticles were performed by microscopic analysis. AgNPs were shown to be present in epidermal stem cells, within vascular bundles and in intermembrane spaces. In leaves, they were observed in ribs and stomata. The current and future use of AgNPs in agricultural sciences opens up the possibility of studying their effects on different plant species.